Visually Impaired Persons and Access to Copyrighted Works: The Indian Roadmap - Vaidyanathan, Saraswathy; Girish, Anjana (UI Scholars Hub, 2021)
The copyright regime poses challenges to visually impaired persons, such as the inability to access books written in a format suitable for their reading needs. Therefore, in 2013, the Marrakesh Treaty to Facilitate Access to Published Works for Blind Persons, Visually Impaired, or Otherwise Print Disabled was carried out to resolve these challenges. India has adopted certain exceptions in its copyright regime, which facilitate access to the visually impaired. However, the beneficial effects of these provisions remain debatable. This research is based on an empirical study conducted on the effectiveness of the provisions of the Indian Copyright Act on facilitating access to copyrighted works to visually impaired persons. It argues that although India has hit the mark in drafting suitable legislation, there are deficiencies in its implementation. Therefore, as the first country to ratify the Marrakesh Treaty, effective implementation of the provisions is needed to make it an illustrious example to the world.